MODELING AND ANALYSIS OF RETAINING WALL STRUCTURE AT CRUSHING PLANT AT COAL PORT - Muhammad Shohib; Andi Patriadi; Jiden Desta Mahendro; Adilat Ahmad Firdausyi; Shinta Berlinda Wulandari; Aviska Triayaska; Izzul Manjulang Tunggal Panggayo; Muhammad Mashadi; Abdul Khohar (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
The development of coal port infrastructure requires a safe and efficient structural design to support the increase in production capacity, one of which is through the construction of a crushing plant equipped with a retaining wall. This study aims to analyze the structural strength and stability of soil retaining walls that function to withstand lateral soil pressure and dynamic loads due to dumping activities in the Run of Mine (ROM) hopper area. Structural modeling was carried out using SAP2000 software by considering dead load, live load, and active ground pressure. The analysis of the bearing capacity of the foundation was carried out using the Converse-Labare, Los Angeles Group Formula, and the Seiler-Keeney Formula, while the bending moment control was evaluated against the cracking moment capacity based on the specifications of the reinforced concrete pile. In addition, the analysis process refers to national and international planning standards, namely SNI 8460:2017 regarding geotechnical planning, SNI 2847:2019 regarding structural concrete requirements for buildings, and SNI 1727:2020 regarding minimum loads. Wall stability standards such as USACE EM 1110-2-2502 and AASHTO LRFD lateral load guidelines are also used as a reference in evaluating the stability of bolsters, shears, and bearing capacity of pile foundations. The results of the analysis show that the retaining wall structure model consists of three main parts, namely Section 1 and 2 with a length of 10 meters and Section 3 with a length of 18 meters. In the 10-meter retaining wall structure, the total weight of the structure is 365,665 tons with a combined carrying capacity of 405,046 tons of mini square pile and spun pile, which shows a safe condition against vertical loads. The moment control results showed that the maximum working moment on the mini pile (23.842 kN·m) and the D600 spun pile (101.3516 kN·m) was smaller than the permissible crack moment, so the structure was declared safe against bending cracking. In the 18-meter retaining wall model, similar results were obtained with a larger foundation carrying capacity than the total weight of the structure and the bending moment of work that is still below the material crack limit according to the design standards used.